Macrocyclic Carriers for Separation of ReO-4 in Bulk Liquid Membrane - MoayyedG. Jalhoom et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Transport experiments a cross bulk liquid membranes (BLMs) are presented . The competitive transport of ReO-4 ions through a BLM with dibenzo-18-crown-6(DB18c6) , di cyclohexyl- 18- crown-6 ( DCH18C6, diaza-18-crown-6(DA18C6) and kryptofix 2.2.2 (Cryp2.2.2)were investigated .The effect of stirring speed , type of carrier and type of organic solvent on the transport of ReO-4 ions from source phase consist of 0.001 M from KReO4 in 10 ml of double distilled deionized water to receiving phase consisted of 10 ml of double distilled deionized water at PH = 3.2-3.7 a cross organic phase consist of 0.01 M of Crown ether in 40 ml of organic solvent . The permeability and the rate transport of ReO-4 ions were determined,they are founed to be favrouble and more acceptable with the compound dicyclohexyle 18-Crown-6 as Carrier,1,2-dichloro ethane as organic solvent and 100 rpm rat speed in this model.